Microwave Dielectric Properties of Low-Temperature Sintered Bi2[Zn1/3(Nb1-xTax)2/3]2O7 - Yeo, Dong-Hun; Shin, Hyo-Soon; Park, Zee-Hoon (Asian Journal of Chemistry, 2014)
After Bi2(Zn1/3Nb2/3)2O7 (BZN) and Bi2(Zn1/3Ta2/3)2O7 (BZT) were calcined at 900 ºC and then sintered at 900 ºC, respectively, microwave dielectric properties of BZN were quality factor (Qf0) = 3,584 GHz, dielectric constant (er)=77 and temperature coefficient of resonant frequency (tf) = -34.2 ppm/ºC. Those of BZT were Qf0 = 3,640 GHz, er = 64 and tf = 2.2 ppm/ºC. These two bismuth (Bi) based composition are known to be adequate for microwave application. However BZT has superior Q·f0 to BZN, but higher sintering temperature which make BZT difficult for co-firing with Ag electrode, while BZN can be co-fired with Ag electrode, but lower Qf0 than BZT. Therefore in this study, Bi2[Zn1/3(Nb1-xTax)2/3]2O7 (BZNT), solid solution between BZT and BZN, was synthesized and sintered at various temperatures for investigation. As amount of Ta substituting Nb increased, sintered density and Q·f0 increased while er decreased. Temperature coefficient of resonant frequency (tf) changed from negative to positive region. When BZNT (x = 0.5) was sintered at 900 ºC, dielectric properties were Qf0 = 4,229 GHz, er = 71 and tf = 24.7 ppm/ºC.